2003
DOI: 10.1124/jpet.103.056036
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effects of Novel A2B Adenosine Receptor Antagonists

Abstract: Caffeine, an adenosine A 1 , A 2A , and A 2B receptor antagonist, is frequently used as an adjuvant analgesic in combination with nonsteroidal anti-inflammatory drugs or opioids. In this study, we have examined the effects of novel specific adenosine receptor antagonists in an acute animal model of nociception. Several A 2B -selective compounds showed antinociceptive effects in the hot-plate test. In contrast, A 1 -and A 2A -selective compounds did not alter pain thresholds, and an A 3 adenosine receptor antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 32 publications
(41 reference statements)
3
111
2
Order By: Relevance
“…Caffeine (10 mg/kg) administered alone in the tail immersion test produced a pronociceptive effect and abolished the antinociceptive effect of paracetamol. In the hot-plate test caffeine alone also did not produce an antinociceptive effect, in contrast to the results reported by Abo Salem et al (2004). When administered in combination with paracetamol, caffeine again inhibited the effects of paracetamol.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Caffeine (10 mg/kg) administered alone in the tail immersion test produced a pronociceptive effect and abolished the antinociceptive effect of paracetamol. In the hot-plate test caffeine alone also did not produce an antinociceptive effect, in contrast to the results reported by Abo Salem et al (2004). When administered in combination with paracetamol, caffeine again inhibited the effects of paracetamol.…”
Section: Discussioncontrasting
confidence: 88%
“…Abo-Salem et al (2004) reported that PSB1115 at 10 mg/kg did not produce significant antinociception by itself in the hot plate test, but significantly …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A 2 receptor agonists are also pronociceptive in a mechanical paw pressure test in the rat (Taiwo and Levine, 1990), though these early studies used very poorly selective drugs. Added to this, the recent development of highly selective A 2B antagonists shows that these compounds have antinociceptive activity in the hot-plate test (Abo-Salem et al, 2004) and thus the A 2A -A 2B selectivity of the pharmacological tools used in nociceptive studies also needs to be considered alongside their A 1 activity. The literature on A 2A receptor agonists is therefore contradictory although microdialysis studies of the release of adenosine in the hind paw in response to formalin has led to the proposal that adenosine may act at pronociceptive A 2A receptors.…”
Section: Pharmacological Studies With Adenosine a 2a Receptor Agonistmentioning
confidence: 99%